2016
DOI: 10.3758/s13414-016-1150-3
|View full text |Cite
|
Sign up to set email alerts
|

Framing visual roll-motion affects postural sway and the subjective visual vertical

Abstract: Effects of visual roll-motion on postural sway and the subjective visual vertical (SVV) often is studied using mechanical devices, whereas electronic displays offer cheaper and more flexible alternatives. These devices typically emit and reflect light scattered by the edges of the screen, providing Earth-fixed cues of verticality. These cues may decrease the effects of rotating stimuli, a possibility that has not been studied explicitly before in one experimental design. We exposed 16 participants to a visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…In the case of a square frame, the visual vertical estimate is biased by the frame orientation, which is known as the rod-and-frame effect. The frame effect can be robust and, for example, significantly decrease SVV errors induced by rotating backgrounds ( 122 , 123 ). This visual effect for the most part depends on the viewing distance and the head tilt position.…”
Section: Neurobehavioral Aspects Of Upright Perceptionmentioning
confidence: 99%
“…In the case of a square frame, the visual vertical estimate is biased by the frame orientation, which is known as the rod-and-frame effect. The frame effect can be robust and, for example, significantly decrease SVV errors induced by rotating backgrounds ( 122 , 123 ). This visual effect for the most part depends on the viewing distance and the head tilt position.…”
Section: Neurobehavioral Aspects Of Upright Perceptionmentioning
confidence: 99%
“…Cette étude pilote précède la tenue d'une expérimentation plus large avec des effectifs plus importants intégrant des individus situés aux extrêmes du continuum (i.e., fortement DC ou IC). Nous espérons dès lors pouvoir observer des effets plus marqués de l'inclinaison d'une scène allocentrée sur la VS. En outre, nos scènes allocentrées ayant la particularité d'être dynamiques, il serait intéressant d'enrichir nos données de dépendance à l'égard du champ issues du RFT par un test de type « visual roll-motion » (Lubeck, Bos, & Stins, 2016). Les effets de la mise en rotation d'un nuage de points sur la VS pourraient être croisés avec les données issues du RFT et nous donner une information plus précise sur la sensibilité individuelle de nos participants aux perturbations issues de l'environnement visuel proche.…”
Section: Discussionunclassified
“…Duration is the total time the button is pressed during each trial. Vection is by nature a subjective sensation, and the approach of button pressing during the trial and magnitude estimation methods after each session allows us to quantify it using well-established methods [20][21][22][23][24]38].…”
Section: Plos Onementioning
confidence: 99%
“…Investigating the potential role of consciousness in quiet standing requires a setup with low-amplitude, low-frequency conditions. Previous studies have shown that vection can impact postural response [20][21][22][23][24]; however, the adopted visual-stimulus speed was high in order to create conditions where vection would be evoked and constant speed or direction (contraction, expansion, rotation) were used to maintain a continuous feeling of vection. Such rapid visual stimuli lie far outside the range of natural human motion, and therefore evoke an acute, high-alert body reaction.…”
Section: Introductionmentioning
confidence: 99%